Peran Panti Asuhan dalam Menanamkan Pendidikan Karakter Anak Asuh: (Studi Kasus Panti Asuhan 'Aisyiyah Putri di Kelurahan Tiakar Hilir, Kecamatan Payakumbuh Utara, Kota Payakumbuh) - Utri Raihani; Hidayani Syam; Susi Afrita (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Conclusions from initial observations, it appears that foster children show a number of personality traits that are not in line with the expected cooperative attitude and religious values. From the perspective of religious values and mutual cooperation, this research aims to explain character education initiatives as well as supporting and inhibiting factors. In the research design, qualitative descriptive methods will be used. Data collection methods include observation, interviews, and documentation. Displaying data and making conclusions from data analysis through reduction. Based on the research results, the task of the Aishiya Putri Orphanage is to teach religious principles, character education, and cooperative behavior to its foster children through the use of policies, procedures, guidelines, and punishments that can help foster cooperative behavior and religious character. The analysis and conclusions of this research center on the contribution made by cooperative orphanages to the development of the younger generation as a whole by offering character education as well as faith-based correctional and rehabilitation services. However, both motivational and disincentive elements have an impact on character education initiatives.